Perforated Jejunal Diverticula Secondary to a Large Faecolith: A Rare Cause of the Acute Abdomen - Peter John Webster; Abigail Hyland; Amarvir Bilkhu; Satheesh Hanavadi; Narinder Sharma (Case Reports in Surgery)
Jejunal diverticula are uncommon and usually asymptomatic. Very rarely, they can lead to acute complications such as bleeding, obstruction, and perforation. This report describes our experience of a case of jejunal diverticula perforation secondary to a large faecolith, with particular focus on the aetiology and management of this rare condition.